Tibolone – tissue specific activity - Palacios, Santiago (Menopause Review/Przegląd Menopauzalny, 2002)
Tibolone’s tissue specific activity may be explained by the interplay of several mechanism, such as the metabolic conversion of tibolone to compounds with different biological activity, the classical interaction with the steroid receptor and the specific local metabolism, within the target tissue. Therefore, the tissue response and thus the clinical effect produced by tibolone in a given tissue seem to depend on the predominating mechanism and interactions present in that tissue.